2022
DOI: 10.1111/jcal.12751
|View full text |Cite
|
Sign up to set email alerts
|

How should webcams be used in online learning under COVID‐19: A co‐orientation analysis of teachers' and students' perceptions of student social presence on webcam

Abstract: Background The existing literature has predominantly focused on instructor social presence in videos in an asynchronous learning environment and little is known about student social presence on webcam in online learning in the context of COVID‐19. Objectives This paper therefore contrasts students' and teachers' perspectives on student social presence on webcam in synchronous online teaching through co‐orientation analysis. Methods Data were collected through an online questionnaire with 14 statements that mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Drawing from this study, we argue that raising teachers' consciousness about features conducive to rapport building is crucial. For instance, discussing research on the use of the webcam for teaching a foreign language online [19,42,43] and the use of comments and their impact on social presence and rapport, is valuable. The results of this study showed that, to enhance the quality of online teaching, training should include discussions based on theoretical models on how to effectively foster rapport, social presence, and learner autonomy in an online setting.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing from this study, we argue that raising teachers' consciousness about features conducive to rapport building is crucial. For instance, discussing research on the use of the webcam for teaching a foreign language online [19,42,43] and the use of comments and their impact on social presence and rapport, is valuable. The results of this study showed that, to enhance the quality of online teaching, training should include discussions based on theoretical models on how to effectively foster rapport, social presence, and learner autonomy in an online setting.…”
Section: Discussionmentioning
confidence: 99%
“…This could arise from the more relaxed learning space Gather created as “it feels more like a game rather than lecture/class” and “the interface is less static and more colorful”, as indicated in the open-ended questions. This correlates to the goal in game-based learning as a more relaxed and open atmosphere in the game clearly also encouraged learners to engage in interaction and be less afraid to make mistakes. , …”
Section: Results and Discussionmentioning
confidence: 78%
“…This correlates to the goal in game-based learning as a more relaxed and open atmosphere in the game clearly also encouraged learners to engage in interaction and be less afraid to make mistakes. 67,68 In open ended questions, students expressed that the escape room format is a "more interactive" way of presenting lab-related questions, and they are "more engaged due to the need of communication to solve the problems". In addition, the colorful interface of online platforms is also believed to motivate students to access online learning.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the same sense, teachers should take into account the perspective of students to determine the types of activities that are suitable for the use of webcams in online learning, despite the perceptual gaps between teachers and students regarding the use of webcam, teachers being more positive about the impact of its use on learning. Usually, reflective tasks and oral evaluations were considered suitable for the use of webcams by students (Yeung, Yau, & Lee, 2022).…”
Section: Synthesis Of Concerns Regarding Online Education In the Univ...mentioning
confidence: 99%